2019
DOI: 10.1371/journal.ppat.1008128
|View full text |Cite
|
Sign up to set email alerts
|

Amblyomma americanum ticks utilizes countervailing pro and anti-inflammatory proteins to evade host defense

Abstract: Feeding and transmission of tick-borne disease (TBD) agents by ticks are facilitated by tick saliva proteins (TSP). Thus, defining functional roles of TSPs in tick evasion is expected to reveal potential targets in tick-antigen based vaccines to prevent TBD infections. This study describes two types of Amblyomma americanum TSPs: those that are similar to LPS activate macrophage (MΦ) to express pro-inflammation (PI) markers and another set that suppresses PI marker expression by activated MΦ. We show that simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 87 publications
(60 reference statements)
0
14
0
2
Order By: Relevance
“…Serpins secreted in tick saliva can facilitate blood meal uptake not only by inhibiting coagulation but also by suppressing host inflammatory responses ( 37 , 72 , 74 ). Therefore, we next investigated whether Iripin-3 attenuates pro-inflammatory cytokine production by LPS-stimulated BMDMs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serpins secreted in tick saliva can facilitate blood meal uptake not only by inhibiting coagulation but also by suppressing host inflammatory responses ( 37 , 72 , 74 ). Therefore, we next investigated whether Iripin-3 attenuates pro-inflammatory cytokine production by LPS-stimulated BMDMs.…”
Section: Resultsmentioning
confidence: 99%
“…The decreased IL-6 production was probably caused by the inhibition of Il6 transcription and not by reduced viability of macrophages, since the metabolic activity of macrophages remained unchanged in the presence of Iripin-3. Several tick serpins have been shown to inhibit IL-6 transcription and secretion ( 37 39 , 74 , 98 ), which can occur as a result of serpin-mediated inhibition of proteases such as cathepsin G and cathepsin B ( 37 ). However, the inhibition of pro-inflammatory cytokine production does not have to be dependent on serpin anti-protease activity because some serpins, like Iris and α-1-antitrypsin, can alter pro-inflammatory cytokine production by binding to immune cells via exosites ( 98 , 99 ).…”
Section: Discussionmentioning
confidence: 99%
“…Scientific approaches to understand the interaction between the fish and this resilient ectoparasite has included searches for parasite substances that manipulate the host. Following the identification of PGE 2 in lice secretory/excretory products, a pivotal role of PGE 2 as a salmon louse immune-dampening substance was suggested [ 36 ] based on its role in immunomodulation by other endo- and ectoparasites [ 24 , 26 , 28 30 , 67 ]. However, the exact role of PGE 2 in the salmon louse host–parasite interaction remains elusive due to technical difficulties obtaining pure secretions from salmon lice glands.…”
Section: Discussionmentioning
confidence: 99%
“…However, uncovering the role of PGs is complicated by their diverse roles and the fact that these compounds are produced by both the host and the parasite [ 27 ]. In blood-feeding arthropods such as ticks, PGs are suggested to be involved in vasodilation and immune modulation in the host, as high concentrations of PGE 2 are found in tick saliva [ 28 30 ]. Both PGE 2 and PGD 2 have been detected in gland secretions from the fish tapeworm Diphyllobothrium dendriticum when incubated in serum from a host fish [ 24 ], and in vitro studies have suggested that PGE 2 derived from the tapeworm Schistocephalus solidus have the potential to modulate host leukocyte viability and reactive oxygen species production [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found five IGFBP-rP sequences, three of which were suppressed, and two that were enhanced. We have recently shown that some of the tick IGFBP-rPs, which bind insulin [ 191 ], are involved in tick evasion of host inflammation defense [ 192 ]. Interestingly, RNAi silencing mediated disruption of A. americanum IGFBP-rP1 and IGFBP-rP6S and L significantly affected tick fitness and feeding success [ 193 ] demonstrating the significance of this protein in tick feeding physiology.…”
Section: Resultsmentioning
confidence: 99%